Muslims and the Gospel Bridging the Gap - Miller, Roland E. (Book collections on Project MUSE., 2005)
"The author's five decades of personal experience leads him to conclude that it is possible to be a witness to the Gospel and be a friend to Muslims at the same time. The author outlines key factors in the Muslim understanding of the Gospel, examines some bridges, and defines the art of sharing. He concludes by assessing the possibilities of such a mission"--Amazon.com.